Important Properties of the SMA Asphalts – Stone Mastic Asphalts - Hrapović, Kerim (European Journal of Science, Innovation and Technology, 2024)
For more than 40 years, Stone Mastic Asphalt has developed into an extremely successful asphalt construction method on a wide variety of traffic surfaces, not only in Austria and Germany, but worldwide. Stone Mastic Asphalt is based on the principle of a "self-supporting chippings framework" as well as on a high binder content through the use of fibrous material. The low void content makes the finished SMA layer practically impermeable to water. With properties such as versatile, durable, stable, wear-resistant, deformation-resistant and fatigue-resistant, Stone Mastic Asphalt meets the requirements of a modern road network, and road users, municipalities and the asphalt industry can all benefit from this.